The Kohs' blocks test as an important instrument to investigate the visuo-spatial impairments in myotonic dystrophy: part I. Quantitative and qualitative analysis - CRISTINA MARIA DUARTE WIGG; LUIZ ANTONIO ALVES DURO (Arquivos de Neuro-Psiquiatria)
This study presents the performance of 39 cases of myotonic dystrophy on Kohs' blocks test (21 females and 18 males, age range from 9 to 70 years). On this test, the patients have to reproduce figures from models previously showed to them. Some of the patients had some kind of professional activity, while others had never exerted a professional occupation. The patients denoted considerable difficulty to perform the test. Some cases constructed entirely different figures in comparison to the presented drawings, translating visuo-spatial and constructional disabilities. The performance was insufficient in 71.4 % of the cases. These cases solved less than 50% of the test. The levels of analysis and synthesis were severely impaired. A total of 18 cases got less than 10 points, not reaching 20% of the test. The results showed the sensitivity of this test in detecting visuo-spatial impairment in myotonic dystrophy.